Analisis Volume Penjualan, Biaya Operasional dan Harga Kamar terhadap Laba Bersih (Studi Empiris pada Grand Dian Hotel Brebes Tahun 2017 – 2018) - Akhmad Saripin; Hilda Kumala Wulandari; Azizah Indriyani; Anisa Sains Kharisma; Siti Musdalifah (Journal of Accounting and Finance (JACFIN), 2019)
The company increases every year, this has an impact on corporate competition, one of them on companies in the service sector. Therefore, companies are racing to increase profit as much as possible. The purpose of this study is to determine and analyze the effect of: sales volume on net income, operating cost on net income, room price on net income and sales volume, operating cost and room price on net incomet. The population in this study is the 2017-2018 annual financial statements. Sample selection uses a purposive sampling technique of 120 samples. The data uses are secondary data from the Grand Dian Hotel Brebes financial report for 2017-2018. Hypothesis testing uses SPSS. The theoretical basis uses is the theory of earning, sales volume, operating cost and price. The result show that: the sales volume has a significant effect on net income partially, operating cost has a significant effect on net income partially, the room price has a significant effect on net income partially, sales volume, operating cost and room price have a significant effect on net income simultaneously